Cross-Sectional Analysis of Baseline Visual Parameters in Subjects Recruited Into the RESCUE and REVERSE ND4-LHON Gene Therapy Studies. Issue 3 (September 2021) - Moster, Mark L.; Sergott, Robert C.; Newman, Nancy J.; Yu-Wai-Man, Patrick; Carelli, Valerio; Bryan, Molly Scannell; Smits, Gerard; Biousse, Valérie; Vignal-Clermont, Catherine; Klopstock, Thomas; Sadun, Alfredo A.; DeBusk, Adam A.; et al.
Abstract : Objective: This report presents a cross-sectional analysis of the baseline characteristics of subjects with Leber hereditary optic neuropathy enrolled in the gene therapy trials RESCUE and REVERSE, to illustrate the evolution of visual parameters over the first year after vision loss. Methods: RESCUE and REVERSE were 2 phase III clinical trials designed to assess the efficacy of rAAV2/2- ND4 gene therapy in ND4 -LHON subjects. At enrollment, subjects had vision loss for ⩽6 months in RESCUE, and between 6 and 12 months in REVERSE. Functional visual parameters (best-corrected visual acuity [BCVA], contrast sensitivity [CS], and Humphrey Visual Field [HVF]) and structural parameters assessed by spectral-domain optical coherence tomography were analyzed in both cohorts before treatment. The cross-sectional analysis of functional and anatomic parameters included the baseline values collected in all eyes at 2 different visits (Screening and Inclusion). Results: Seventy-six subjects were included in total, 39 in RESCUE and 37 in REVERSE. Mean BCVA was significantly worse in RESCUE subjects compared with REVERSE subjects (1.29 and 1.61 LogMAR respectively, P = 0.0029). Similarly, mean CS and HVF were significantly more impaired in REVERSE vs RESCUE subjects ( P < 0.005). The cross-sectional analysis showed that the monthly decrease in BCVA, ganglion cell layer macular volume, and retinal nerve fiber layer thickness was much more pronounced in the first 6 months after onset (+0.24 LogMAR, −0.06 mm 3, and −6.00 μm respectively) than between 6 and 12 months after onset (+0.02 LogMAR, −0.01 mm 3, and −0.43 μm respectively). Conclusion: LHON progresses rapidly in the first months following onset during the subacute phase, followed by relative stabilization during the dynamic phase.